Mechanical and microstructural evolution of 3D printed concrete with polyethylene fiber and recycled sand at elevated temperatures. (26th July 2021) - Xiao, Jianzhuang; Han, Nv; Zhang, Lihai; Zou, Shuai
Highlights: 3DPC suffered delamination at high temperature instead of spalling failure. Temperature effects on the microstructure of 3DPC are expressive over 400 ℃. Recycled sand and PE fiber are proved to alleviate delamination of 3DPC. Abstract: 3D printed concrete (3DPC) has become increasingly popular in the last decade. However, the mechanical and microstructural evolution of the 3DPC under extremely high-temperature environments has not been fully understood. The purpose of this study is to experimentally investigate the influence of recycled sand and polyethylene (PE) fiber on the mechanical properties and pore structure of the 3DPC under high temperatures. A series of compressive, flexural, and CT scanning tests were conducted for 3DPC specimens under 20 °C, 200 °C, 400 °C, 600 °C, and 800 °C, respectively. It shows that there is a similar degradation trend of the compressive and flexural strengths of 3D printed and mold-casted specimens with the same mixture at elevated temperatures. 3DPC specimens delaminated through the interface between layers and strips in the layer at 600 °C and 800 °C, respectively, due to the weak adhesion between layers and strips. The addition of recycled sand and PE fiber into the 3DPC could modify its pore structure and mitigate the risks of explosive spalling.